Li2SnO3 Anode Synthesized via Simplified Hydrothermal Route Using Eco-Compatible Chemicals for Lithium-Ion Battery - Zakuan, Noor Syuhada; Woo, Haw Jiunn; Teo, Li Ping; Kufian, Mohd Zieauddin; Osman, Zurina (Electrochemical Society, 2019)
Low cost group IV element (Sn) based-materials can provide high capacity substitute for lithium-ion batteries (LIBs). Tin based oxide Li2SnO3 was successfully synthesized via low temperature hydrothermal route without further calcination and used as anode materials in LIBs. In this work, eco-compatible chemicals Tin (IV) oxide, SnO2 and lithium hydroxide monohydrate, LiOH.H2O were used as starting reagents. XRD results show that the monoclinic crystal structure Li2SnO3 is of high purity. This finding agrees with TEM micrographs that display nano-sized particle with interplanar spacing corresponding to (110) and (101) lattice planes. The narrow particle size distribution of 50-60 nm predicts the outstanding performance of LIBs. The first cycle discharge capacity is 2582 mAhg-1. However, the cycling performance only maintain in between 180-290 mAhg-1 up to 50 cycles. The mechanism of Li reactivity in Li2SnO3 is through Li-Sn alloying/de-alloying process. The diffusion coefficient of Li+ ion is calculated as 2.144 × 10-13 cm2 s-1. Impedance studies of LIB cells proof the formation of SEI at the first cycle and explains the poor stability of the cells.